NO2 Adsorption Sensitivity Adjustment of As/Sb Lateral Heterojunctions through Strain: First Principles Calculations - Li Yang; Dengkui Wang; Dan Fang; Hao Yan; Yingjiao Zhai; Xueying Chu; Jinhua Li; Xuan Fang (Crystals, 2023)
Strain engineering is an effective way to adjust the sensing properties of two-dimensional materials. In this paper, lateral heterojunctions (LHSs) based on arsenic and antimony have been designed along the armchair (AC) or zigzag (ZZ) edges. The adsorption and sensing characteristics of As/Sb LHSs to NO2 before and after applying different types of strain are calculated by first principles. The band gaps of all As/Sb heterostructures are contributed by As-p and Sb-p orbitals. In addition, the adsorption energy of As/Sb ZZ-LHS with −4% compression strain is the largest. Furthermore, its work function changes significantly before and after the adsorption of NO2. Meanwhile, strong orbital hybridizations near the Fermi level are observed and a new state is yielded after applying compressive strain. These results indicate that the As/Sb LHS with ZZ interface under −4% compression strain possesses the best sensing properties to NO2. This work lays the foundation for the fabrication of high-performance NO2 gas sensors. High-performance gas sensors can be used to track and regulate NO2 exposure and emission, as well as to track NO2 concentrations in the atmosphere and support the assessment of air quality.